Biodiversidade de Selenastraceae (Sphaeropleales, Chlorophyceae) : características morfológicas e sequenciamento dos marcadores moleculares 18S rDNA, rbcL e ITS como base taxonômica tradicional - Silva, Thaís Garcia da (Universidade Federal de São Carlos, 2016)
The phylogeny of the family Selenastraceae was investigated by light microscopy, molecular analysis of 18S rDNA, rbcL, ITS1-5.8S-ITS2 and ITS-2 markers. Several morphological features traditionally used for identification of genera and species were investigated. All Selenastraceae strains studied presented naked pyrenoids within the chloroplast, except for Chlorolobion, which presented starched pyrenoid. Molecular analysis showed that no isolated morphological criteria considered so far is significant for the systematic of Selenastraceae, but a set of characteristics may be appropriate to identify species of genera Ankistrodesmus, Chlorolobion, Kirchneriella, Raphidocelis and Tetranephris. Phylogenetic analyses showed that genera Monoraphidium, Kirchneriella and Selenastrum are polyphyletic and not distinguishable as separate genera. The Selenastrum morphotype revealed three different molecular lineages, leading to the description of two new genera, Curvastrum gen. nov and Messastrum gen. nov. In addition, molecular phylogenetic analysis revealed four lineages assigned to Kirchneriella orphotype, leading to the description of five new species: Genus 1 sp. nov. 1, Genus 2 sp. nov. 1, Genus 2 sp. nov. 2, Raphidocelis sp. nov. and Tetranephris sp. nov.
Keywords: Taxonomia; Sistemática molecular; Selenastraceae; Biodiversidade; Filogenia; CIENCIAS BIOLOGICAS